Geochemical characteristic of metamorphic rocks from South Sulawesi, Central Java, South and West Kalimantan in Indonesia - Setiawan, Nugrobo Imam (ASEAN engineering journal)
This study describes the geochemical character of the metamorphic rocks to consider the original rock composition and ascertain their relationship to the tectonic environments in the area.